SnO2:Eu nanocrystallites in SnO2 monolithic xerogels - Ribeiro, Sidney J.L. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP] (Elsevier, 1992)
By simple room temperature broad band time-resolved spectroscopy it was possible to discriminate different Eu3+ spectra in SnO2 monolithic gels obtained by a sol-gel synthetic route. Nanocrystalline domains of the cassiterite-like SnO2:Eu could be easily identified in the transparent medium. From X-ray diffraction profiles a mean particle radius of 2.2 nm was estimated. © 1992.